Knowledge and Behaviour of Diabetic Patients to Prevent Diabetic Foot Complications - Valčiukienė, Lina; Paškevičė, Alma; Stauskienė, Kristina (Slauga. Mokslas ir praktika, 2024)
This article highlights the importance of understanding the knowledge and behaviour of diabetic patients in preventing diabetic foot complications. Diabetic foot complications can be largely prevented by educating patients and proper foot care. Adequate patient knowledge of risk factors, early signs of complications and preventive measures, combined with positive health behaviours, can significantly reduce the incidence of foot ulcers and amputations. However, despite clear scientific evidence supporting the benefits of patient education, many individuals with diabetes lack the necessary knowledge and often fail to engage in preventive behaviours. This paper presents the results of a study comparing the knowledge and behaviour of Lithuanian and Dutch diabetes patients. The study used a quantitative questionnaire survey method with a purposive sample of 86 diabetic respondents. The sample consisted of 43 patients from each country. . The results of the study were summarised revealing that respondents from both countries expressed interest in learning more about several key areas including: foot care hygiene; appropriate footwear; injuries and their prevention; foot problems and the steps to be taken;, and when to seek medical assistance.